Семантико-стилістичні функції хроматизмів як засіб формування національно-мовної картини світу - Формарова, С.В.; Базик, О.И. (Культура народов Причерноморья, 2004)
Интерес к цветообозначениям обусловлен самой жизнью. Семантика цветообозначений в последнее время развилась в особую область в науке о языке, т.к. развитие цветообозначений тесно связано с восприятием окружающего мира.
Настоящая статья является попыткой систематизации исследований лингвистов, философов и психологов относительно теории цвета и определения семантики цветообозначений. The interest to the colour is conditioned by life. Last time the semantic of the colour terms developed at the special region in the linguistics’ science. Development of the colour terms is connected with the perception of the surroundings.
This article is systematizatiion the investigations by linguistis philosophers and psychologists to the theory of the colour terms and determination of the semantic of the colour terms.